The beneficial effects of tetracosanol on insulin-resistance by insulin receptor kinase sensibilisation. (April 2015) - Hsu, C.Y.; Shih, H.Y.; Chang, Y.C.; Huang, Z.L.; Tsai, M.J.; Chia, Y.C.; Chen, C.; Lai, Y.K.; Weng, C.F.
Abstract: In this study, we investigated whether tetracosanol, an aliphatic alcohol isolated from Saccharum sinense, enhances insulin receptor kinase activity to exhibit an insulin synergistic effect in vitro and in vivo . The insulin plus tetracosanol enhanced insulin receptor kinase showed that AKT activity was down-regulated by S961 in differentiated L6 myotubes. Meanwhile, insulin plus tetracosanol restored the ability of glucose transporter translocation and glucose uptake in differentiated myotubes with S961-induced insulin resistance in vitro . The modification of carbon chain lengths and the hydroxyl group of tetracosanol showed that it served as a critical chemical structure for the glucostasis effect in vivo. This study provides new evidence to show that tetracosanol can improve glycaemic control via insulin receptor kinase activity induced and leads to the enhancement of glucose transporter translocation to improve glucose uptake. The hydroxyl group of tetracosanol plays a critical role for insulin receptor kinase activity.